Physiological and Transcripts Analyses Reveal the Mechanism by Which Melatonin Alleviates Heat Stress in Chrysanthemum Seedlings - Xing, Xiaojuan; Ding, Yurong; Jin, Jinyu; Song, Aiping; Chen, Sumei; Chen, Fadi; Fang, Weimin; Jiang, Jiafu (Frontiers in Plant Science, 2021)
Heat stress limits the growth and development of chrysanthemum seedlings. Although melatonin (MT) has been linked to the heat stress response in plants, research on the underlying molecular mechanisms is scarce. In this study, the regulatory networks of MT on heat stress in chrysanthemum seedlings were explored. Physiological measurements suggested that MT not only reduced malondialdehyde accumulation, hydrogen peroxide content, and superoxide anion free radical generation rate, but also significantly promoted osmotic regulation substance synthesis (proline and soluble protein), antioxidant accumulation (GSH and AsA), and the antioxidant enzyme activities (SOD, POD, CAT, and APX) in chrysanthemum leaves under heat stress. Furthermore, MT increased the fresh weight, dry weight, chlorophyll content, photosynthesis rate, and gas exchange indexes. Further, RNA-seq results revealed 33,497 and 36,740 differentially expressed genes in the S/Con and SMT/ConMT comparisons, respectively. The differences in the comparisons revealed that MT regulated heat shock transcription factors (HSFs) and heat shock proteins (HSPs), and the genes involved in Ca2+ signal transduction (CNGCs and CAM/CMLs), starch and sucrose metabolism (EDGL, BGLU, SuS, and SPS), hormone (PP2Cs, AUX/IAAs, EBFs, and MYC2), chlorophyll metabolism (HEMA and PORA), flavonoid biosynthesis (CHS, DFR, and FNS), and carotenoid biosynthesis (DXPS, GGDP, and PSY). MT effectively improved chrysanthemum seedling heat-resistance. Our study, thus, provides novel evidence of a gene network regulated by MT under heat stress.